PENGARUH MEDIA INTERAKTIF WORD WALL BERBASIS TPACK TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK - Aqil Syah Mustofa; Yunita Sari; Jupriyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low learning outcomes of class IV B students in science learning, and class teachers had not implemented digital interactive media, which caused learning to be monotonous. Based on the results of interviews, the average daily test score for students in science and science subjects is still relatively low, namely 70% below the KKM. Based on these findings, the research team conducted a study on how interactive word wall media, in conjunction with the TPACK approach, can enhance student learning outcomes in science and science subjects, particularly in relation to climate change. This research method uses a quantitative method with a pre-experimental type and a one-group pretest-posttest research design. The subjects of this research were 20 class IV B students, 11 men and 9 women. The results of this research showed that interactive word wall media with the TPACK approach influenced student learning outcomes as evidenced by an increase in the average pretest score of 58.75 and posttest of 77.50. Based on the results of the analysis of the paired test or t-test, it was obtained that the significance level (sig) value of 0.00 was greater than the significance level of 0.05, so H0 was rejected and H1 was accepted, which means that the use of interactive media with the TPACK approach had an influence on learning outcomes in learning science and science on climate and its changes. Based on the results of this research, it can be said that interactive word wall media with the TPACK approach has an influence on improving the learning outcomes of class IV B students at Sultan Agung Islamic Elementary School 1.3 in the science subject.